Assessment of water consumption during Ramadan intermittent fasting: Result from Indonesian cross-sectional study - Sunardi, Diana; Chandra, Dian Novita; Medise, Bernie Endyarni; Friska, Dewi; Manikam, Nurul Ratna Mutu; Lestari, Wiji; Insani, Putri Novia Choiri; Ayusari, Amelya Augusthina; Mayasari, Diana; Saftarina, Fitria; Sari, Dina Keumala; Ulvie, Yuliana Noor Setiawati (Frontiers in Nutrition, 2022)
During Ramadan fasting, people are likely to consume water and beverages lower than recommended intake due to the limited time. However, it is necessary to achieve the recommended daily water intake to maintain the hydration status, as well as productivity during fasting. Unfortunately, there is a lack of data on drinking patterns during Ramadan. This study aims to investigate water and beverage intake and drinking patterns to help achieve water requirements during Ramadan among Indonesian adults. This is a cross-sectional study conducted during the Ramadan period from April to May 2021 (Ramadan 1442 Hijri). We used a self-administered questionnaire on drinking habits during Ramadan and utilized a 7-day fluid record (Liq.In 7) to assess water and beverage intake among participants who were managed through online procedure. There were 380 participants from five universities across Indonesia who completed the questionnaire accordingly and then analyzed it. The result shows that total water and beverage intake during Ramadan among participants was below the recommendation [1,670 (1,326–2,034) ml/day]. Among the type of beverages, water is the highest level of consumption [1,262 (983–1,666) ml/day] then followed by sugar-sweetened beverages [200 (91–350) ml/day]. We found a significant difference in water and beverages consumption between time of iftar [474 (375–590) ml/day], nighttime [574 (414–810) ml/day], and suhoor [560 (423–711) ml/day]. From this study, we found that during Ramadan the most common drinking pattern is 2-4-2, but a drinking pattern of 4-2-2 glasses (sequence of four glasses at iftar, two glasses at nighttime, two glasses at suhoor) had a significantly higher chance to adhere with the recommendation of fluid intake compared to other patterns. Therefore, based on this research on water and beverage intake, it is necessary and important to make improvements among Indonesian adults during Ramadan, and the drinking pattern of 4-2-2 glasses may help to achieve the recommended daily water consumption.